A Conceptual Framework for Mobile FinTech Adoption: Integrating TAM-TPB with Technology Readiness Index - Wang, Wei; Kasemwattanasuk, Thannaphat; Chaveesuk, Singha; Rojniruttikul, Nuttawut (My University, 2026)
This study proposes a conceptual framework to examine the adoption of mobile financial technology (FinTech) by integrating the Technology Readiness Index (TRI) with a combined Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB). The framework investigates how technology readiness dimensions, which are optimism, innovativeness, discomfort, and insecurity, influence users’ perceptions of mobile FinTech in terms of perceived usefulness and perceived ease of use. These perceptions subsequently shape users’ attitudes toward using mobile FinTech, which, together with subjective norms and perceived behavioral control, drive the behavioral intention to adopt the technology. A quantitative survey will be conducted and analyzed using Structural Equation Modeling to evaluate how factors influence behavioral intention to adopt mobile financial technology within the integrated TAM, TPB, and TRI framework. Through this integrated approach, the study aims to provide empirical insights that underpin mobile FinTech adoption, enabling service providers and policymakers to design more effective strategies to enhance user acceptance and utilization of mobile FinTech services.
Keywords: Behavioral intention; Mobile FinTech; Technology Acceptance Model (TAM); Technology Readiness Index (TRI); Theory of Planned Behavior (TPB)